The Effect of Different Precursor Concentration on The Synthesis of CaO Nanoparticles with Coprecipitation Methods for Palm Oil Transesterification Catalysis - Novita Andarini; Ria Sherly Farida; Tanti Haryati (Reaktor, 2021)
Calcium oxide nanoparticles was prepared by coprecipitation method using calcium acetate as precursor and calcined at 800 °C for 6 hours. This work studied the effect of different precursor concentrations on the size of calcium oxide obtained and its applicated for palm oil transesterification catalysis. Characteristics of samples were measured by XRD and SEM et al techniques. The results showed that the diffraction pattern of CaO has the same diffraction pattern as the XRD standard diffraction pattern from the Joint Committee on Powder Diffraction Standard (JCPDS). Calcium oxide analysis using SEM shows the morphology of particles that agglomerate almost all variations in precursor concentration. The particle size increases with increasing precursor concentration. The smallest particle size of 55.758 nm was produced on solid CaO from the lowest precursor concentration of 0.05 M. The catalytic activity of activated calcium oxide nanoparticle compound was tested in the production of methyl esters. The conversion of triglycerides in palm oil into methyl esters was 90.34%.Keywords: nanoparticles, calcium oxide, coprecipitation, precursor, catalys, metyl ester